The Possible Role of Telomere Length and Chemokines in the Aging Process: A Transdiagnostic Review in Psychiatry - Valiati, Fernanda E.; Hizo, Gabriel Henrique; Pinto, Jairo Vinícius; Kauer-Sant`Anna, Márcia (Current Psychiatry Research and Reviews, 2019)
Background: Psychiatric disorders are common, reaching a worldwide prevalence of 29.2%. They are associated with a high risk of premature death and with accelerated aging in clinical, molecular and neuroimaging studies. Recently, there is strong evidence suggesting a possible role of telomere length and chemokines in aging processes in psychiatric disorders. Objective: We aimed to review the literature on telomere length and chemokines and its association with early aging in mental illnesses on a transdiagnostic approach. Results: The review highlights the association between psychiatric disorders and early aging. Several independent studies have reported shorter telomere length and dysregulations on levels of circulating chemokines in schizophrenia, bipolar disorder, major depressive disorder, and anxiety disorders, suggesting a complex interaction between these markers in a transdiagnostic level. However, studies have investigated the inflammatory markers and telomere shortening separately and associated with a particular diagnosis, rather than as a transdiagnostic biological feature. Conclusion: There is consistent evidence supporting the relationship between accelerated aging, telomere length, and chemokines in mental disorders, but they have been studied individually. Thus, more research is needed to improve the knowledge of accelerated senescence and its biomarkers in psychiatry, not only individually in each diagnosis, but also based on a transdiagnostic perspective. Moreover, further research should try to elucidate how the intricate association between the chemokines and telomeres together may contribute to the aging process in psychiatric disorders.
Keywords: aging